Comparative evaluation of shear bond strength between titanium-ceramic and cobalt-chromium-ceramic: An in vitro study - Kamal Ramjee Vaska; Chandrasekhar Nakka; K Mahendranath Reddy; Siddesh Kumar Chintalapudi (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of this study was to evaluate and compare the shear bond strength between ceramic layered over titanium and ceramic layered over cobalt-chromium alloy, which are used in the fabrication of screw-retained implant prosthesis. Settings and Design: In-vitro - Comparative study. Materials and Method: A total of 40 samples (20 samples of Titanium in Group 1 and 20 samples of Cobalt-Chromium in Group 2) were fabricated. For all the samples bonding agent was applied on to the sand blasted surface and firing was done at a temperature of 980° C. A layer of opaque was applied using a brush and placed back in the furnace at a temperature of 910° C. Then ceramic was layered on to the surface with putty index as guide and firing was done in the ceramic furnace up to a temperature of 880° C followed by glazing. Shear bond strength was measured using a Universal Testing Machine. Statistical Analyses Used: One sample t-test and paired sample t-test. Results: Descriptive statistics were done to calculate mean differences between groups and samples. The mean bond strength of titanium- ceramic samples was more than those of cobalt-chromium-ceramic samples. Inferential statistics used in the study were one sample t-test for intra-group comparison and paired sample t-test for inter group comparison which showed no statistically significant difference between the two metal types (P value = 0.163). Conclusion: The shear bond strength of ceramic veneered over titanium meets the ISO requirements of minimum shear bond strength between metal-ceramic systems and has achieved the clinically acceptable values. The use of titanium super structure over titanium implants reduces the adverse effects and avoids undesirable effects.